Opioids and the Internet: Convergence of Technology and Policy to Address the Illicit Online Sales of Opioids - Mackey, Tim K (Health Serv Insights, 2018)
The United States is in the midst of an opioid public health emergency, one that is also influenced by a convergence of Internet-based technology, health policy, and the need for stakeholder collaboration and action around the need to combat the illicit online sales of opioids by illegal online pharmacies and digital drug dealers. This risk is not new, however, with calls to actively reduce online opioid availability as online pharmacies use a growing array of digital channels, including search engines, social media platforms, and the dark Web. In response, the US Food and Drug Administration convened a special June 2018 summit bringing together technology companies, government agencies, researchers, and advocacy groups with the goal of collaboratively developing and implementing solutions to tackle the problem. Yet after this meeting, stakeholders remain fragmented in approaches despite the availability of technology that can detect, classify, and report illicit sellers who are in direct violation of Federal law. Despite ongoing challenges, advances in data science and the resources and expertise technology companies can contribute will be a key factor in ensuring that the Internet helps end and not fuel the public health emergency of opioid abuse.